Elements of environmental engineering : thermodynamics and kinetics - Valsaraj, K. T. (CRC Press, 2009)
1- Introduction. 2- Basic chemical thermodynamics. 3- Multicomponent equilibrium thermodynamics. 4- Applications of equilibrium thermodynamics. 5- Concepts from chemical rection kinetics. 6- Applications of chemical kinetics in environmental systems. Appendix.